Highly tough and rapid self-healing dual-physical crosslinking poly(DMAA-co-AM) hydrogel. Issue 52 (7th October 2021) - Lin, Yinlei; Wang, Shuoqi; Sun, Sheng; Liang, Yaoheng; Xu, Yisheng; Hu, Huawen; Luo, Jie; Zhang, Haichen; Li, Guangji
Abstract : Introducing a micelle and LAPONITE® XLG nano-clay into N, N -dimethylacrylamide (DMAA)/acrylamide (AM) copolymerization reactions results in a highly tough and rapid self-healing dual-physical crosslinking poly(DMAA- co -AM) hydrogel. Abstract : Introducing double physical crosslinking reagents ( i.e., a hydrophobic monomer micelle and the LAPONITE® XLG nano-clay) into the copolymerization reaction of hydrophilic monomers of N, N -dimethylacrylamide (DMAA) and acrylamide (AM) is reported here by a thermally induced free-radical polymerization method, resulting in a highly tough and rapid self-healing dual-physical crosslinking poly(DMAA- co -AM) hydrogel. The mechanical and self-healing properties can be finely tuned by varying the weight ratio of nanoclay to DMAA. The tensile strength and elongation at break of the resulting nanocomposite hydrogel can be modulated in the range of 7.5–60 kPa and 1630–3000%, respectively. Notably, such a tough hydrogel also exhibits fast self-healing properties, e.g., its self-healing rate reaches 48% and 80% within 2 and 24 h, respectively.